On the issue of surgical methods for the treatment of dislocation syndrome in supratentorial brain tumors. - Isakov B.M; Mamadaliev A.B; Khakimov M.N; Isakov K.B (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this work, we present the results of our own retrospective studies, the material for which was the case histories and the results of surgical treatment of 43 patients with supratentorial brain tumors with dislocation syndrome. The surgical approach varied depending on the location, volume of formation, general condition of the patient and the degree of dislocation of the brain.